1994
DOI: 10.1056/nejm199402103300602
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Study of Ranitidine for the Prevention of Recurrent Hemorrhage from Duodenal Ulcer

Abstract: For patients whose duodenal ulcers heal after severe hemorrhage, long-term maintenance therapy with ranitidine is safe and reduces the risk of recurrent bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
5

Year Published

1995
1995
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(21 citation statements)
references
References 20 publications
1
15
0
5
Order By: Relevance
“…1,5,6 Maintenance antisecretory therapy is the standard long-term treatment for patients with bleeding ulcers to prevent recurrent bleeding, despite the fact that only two randomized studies have specifically examined this option in patients with peptic ulcer haemorrhage. 7,8 The first study found no significant difference in the rate of recurrent bleeding between ranitidine maintenance therapy and placebo, but the number of bleeding episodes was so small that a treatment benefit could not be demonstrated; 7 the second study reported significantly fewer episodes of haemorrhage amongst patients taking ranitidine maintenance antisecretory therapy when compared with placebo. 8 Helicobacter pylori infection is the main aetiological factor in peptic ulcer disease.…”
Section: Introductionmentioning
confidence: 99%
“…1,5,6 Maintenance antisecretory therapy is the standard long-term treatment for patients with bleeding ulcers to prevent recurrent bleeding, despite the fact that only two randomized studies have specifically examined this option in patients with peptic ulcer haemorrhage. 7,8 The first study found no significant difference in the rate of recurrent bleeding between ranitidine maintenance therapy and placebo, but the number of bleeding episodes was so small that a treatment benefit could not be demonstrated; 7 the second study reported significantly fewer episodes of haemorrhage amongst patients taking ranitidine maintenance antisecretory therapy when compared with placebo. 8 Helicobacter pylori infection is the main aetiological factor in peptic ulcer disease.…”
Section: Introductionmentioning
confidence: 99%
“…O avanço na terapêutica endoscópica possibilitou abordagem da angiodisplasia intestinal. Vários mé-todos têm sido utilizados para hemostasia, tais como: injeção de soluções na submucosa (soro fisiológico, esclerosantes, vasoconstrictores); e métodos térmicos (cautérios monopolar e bipolar, gás Argônio) 4,5,6,7,8,9 . A predominância das lesões no cólon direito significa risco maior de complicações no tratamento das anomalias vasculares.…”
Section: Discussionunclassified
“…1 Despite a decline in the incidence of uncomplicated duodenal ulcer disease, the number of hospital admissions and operations for ulcer haemorrhage in the USA has remained relatively unchanged since the introduction of histamine H 2 -receptor antagonists. 2,3 Most ulcer deaths, of which there are over 4000 annually in the UK, 4 occur as a consequence of upper gastrointestinal bleeding, shown in a recent UK study to have a mortality rate of 14%. 5 Studies have shown that 20±40% of duodenal ulcer patients bleed within 20 years of diagnosis, and that the risk of further haemorrhage then increases to 50% or more.…”
Section: Introductionmentioning
confidence: 99%
“…4,6 Indeed, half of all patients with bleeding have no prior symptoms to indicate ulcer relapse. 2,7 The management of these patients must, therefore, include strategies both to heal the ulcer and minimize the risk of recurrent bleeding. The three main factors implicated in gastroduodenal injury which affect management are gastric acid, nonsteroidal anti-in¯ammatory drug (NSAID) ingestion and Helicobacter pylori infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation